2001
DOI: 10.1099/00221287-147-4-1025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrolysable and condensed tannins on growth, morphology and metabolism of Streptococcus gallolyticus (S. caprinus) and Streptococcus bovis

Abstract: Streptococcus gallolyticus (S. caprinus) was resistant in vitro to at least 7 % (w/v) tannic acid and 4 % (w/v) acacia condensed tannin, levels 10-fold greater than those tolerated by S. bovis. Growth of S. gallolyticus in liquid medium was characterized by a lag period which increased, and a growth rate which decreased, with increasing tannin concentration. S. gallolyticus was also more tolerant to the presence of simple phenolic acid monomers than was S. bovis, but the lag period was still concentration depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 35 publications
(24 reference statements)
4
62
0
Order By: Relevance
“…Regarding fermentation patterns, three divisions for S. bovis are described in literature (Ruoff et al, 1989); among these, the group biotype I is able to ferment mannitol, as isolate 7 from the present study. Tannin tolerance has been described for the genus ) acacia condensed tannin, levels 10-fold greater than those tolerated by S. bovis (O'Donovan & Brooker, 2001). Similarly, Rusniok et al (2010) described the ability of this species to adapt to the presence of tannins in the rumen, due to its capacity to use a broad range of carbohydrates, as found in the present study (Table 1), especially those present in the plant cell wall, and to express several hydrolytic enzymes, including tannases and other phenolic compounds decarboxylases that should contribute to the detoxification of the digestive tract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding fermentation patterns, three divisions for S. bovis are described in literature (Ruoff et al, 1989); among these, the group biotype I is able to ferment mannitol, as isolate 7 from the present study. Tannin tolerance has been described for the genus ) acacia condensed tannin, levels 10-fold greater than those tolerated by S. bovis (O'Donovan & Brooker, 2001). Similarly, Rusniok et al (2010) described the ability of this species to adapt to the presence of tannins in the rumen, due to its capacity to use a broad range of carbohydrates, as found in the present study (Table 1), especially those present in the plant cell wall, and to express several hydrolytic enzymes, including tannases and other phenolic compounds decarboxylases that should contribute to the detoxification of the digestive tract.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Khiaosa-Ard et al (2009) observed that treatments of feed with condensed tannins reduced ruminal fiber and crude protein degradation. However, effectively using feedstuff is still possible, due to the complex microbiota found in the gastro-intestinal tract, whose composition is mainly determined by the available diet (O'Donovan & Brooker, 2001;Ammar et al, 2009;Khiaosa-Ard, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, effects are not the same for all CT as they depend upon its chemical structure [24]. Several ruminal microorganisms have been identified that can tolerat relatively high concentrations of both hydrolysable and condensed tannins (CTs) [34]. However, the mechanism for this tolerance has not been completely elucidated.…”
Section: Anti-nutritive Substancesmentioning
confidence: 99%
“…are generally HT rather than CT. However, S. gallolyticus also demonstrates resistance to Acacia CT (< 4%) in vitro, whereas S. bovis is inhibited at >0.5% (O'Donovan and Brooker, 2001). Whether S. gallolyticus or other rumen microbes have the ability to degrade CT in the rumen is unclear.…”
Section: The Anti-nutritional Effect Of Condensed Tanninsmentioning
confidence: 99%